1990
DOI: 10.1121/1.399682
|View full text |Cite
|
Sign up to set email alerts
|

A general formulation for the sound radiation from rectangular, baffled plates with arbitrary boundary conditions

Abstract: The radiation of sound from a baffled, rectangular plate with edges elastically restrained against deflection and rotation is analyzed. The elastic constants along the contour can be varied to reproduce simply supported, clamped, free, or guided edges as limiting cases. The formulation is based on a variational method for the vibration of the plate, and assumes no fluid loading of the structure. The elastic boundary conditions appear in the Hamiltonian of the plate through a dynamic contribution, which is expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
80
1
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(86 citation statements)
references
References 0 publications
3
80
1
2
Order By: Relevance
“…In mode ( modes. However, the modal resonance frequency for mode (21,1) is 7.6 kHz, which is much lower than the resonance frequency for mode (20,20), i.e. 18.6 kHz.…”
Section: Modified Green's Functionmentioning
confidence: 77%
See 1 more Smart Citation
“…In mode ( modes. However, the modal resonance frequency for mode (21,1) is 7.6 kHz, which is much lower than the resonance frequency for mode (20,20), i.e. 18.6 kHz.…”
Section: Modified Green's Functionmentioning
confidence: 77%
“…Later in [21] it was found that only one set of trial functions was required to represent the plate displacement. Berry et al [20] found that in low-order modes up to the mode (2,2), the simply supported plate has a slightly higher radiation efficiency than that of the clamped plate. For all other modes, the opposite situation applies with a maximum factor of 2.5 (4 dB).…”
mentioning
confidence: 99%
“…The excitation is very often asymmetric in the real vibrating systems and it is very useful to find some asymptotic and approximate formulae for the modal quantities necessary to compute the acoustic power, the acoustic pressure and the structure's vibration velocity including the fluid loading. So far, a number of such formulae have been presented for vibrating circular and rectangular membranes and plates using several approximate methods [1][2][3][4][5][6][7][8][9]. The results obtained by using the exact solutions for the free vibrations have been presented in a few studies [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…One option is to discretise the impacted structure with the Finite Element Method (FEM) as Rabold et al do in [24]. Also, for simple geometries, the equation can be solved with modal analysis, as shown by Chung and Emms [8], Sjökvist et al [26,27] and Berry et al [5] for homogeneous floors with different boundary conditions.…”
Section: Introductionmentioning
confidence: 99%